"Key challenges facing the rule of law in Hong Kong". Issue 1 (22nd June 2021) - Hagiwara, Ryuta
Abstract : Purpose: This paper aims to highlight key challenges to the rule of law in Hong Kong. Design/methodology/approach: This study deploys a historical and legal approach to explore the key challenges to the rule of law in Hong Kong. In particular, this paper analyzes legal conflicts in Hong Kong. Findings: The findings show how the rule of law in Hong Kong has become a prominent battlefield of a constitutional struggle between Hong Kong Law and Chinese Law. Originality/value: This paper hypothesizes that the conflicts arise from the different interpretations and conceptualizations of the rule of law between China and Hong Kong.